Role of sports psychology and sports nutrition in return to play from musculoskeletal injuries in professional soccer: an interdisciplinary approach - Rolli, I.; Carter, J. M.; Close, G. L.; Yangüas, J.; Gomez-Diaz, A.; Medina Leal, D.; Duda, J. L.; Holohan, D.; Erith, S. J.; Podlog, L. (European Journal of Sport Science, 2021)
Musculoskeletal injuries are prevalent in professional soccer and can result in lost training time or match play. It is intuitive that the "return to play" (RTP) pathway will depend, in large part, on the expertise of sports medicine practitioners (e.g. surgeons, physicians, physiotherapists) responsible for player`s recovery. Consensus statements on returning athletes to sport following injury acknowledge the contributions of sport psychology and sports nutrition. However, specific consideration on how to integrate these two recognized - but often overlooked components of injury rehabilitation - into existing sport medicine approaches has yet to be examined. Using a framework of milestones directed by the medical physician and physical trainer, the evidence is summarized and suggestions provided on the integration of sports psychology and sports nutrition into an interdisciplinary RTP approach. We examine recovery from a phase approach (acute injury and functional recovery) to highlight interdisciplinary opportunities in the management of musculoskeletal soccer injuries. An interdisciplinary approach is understood to achieve outcomes that could not be achieved within the framework of a single discipline. The incorporation of sports psychology and nutrition theoretically compliment milestones used in current medically-based RTP models. Our hope is that this article serves as a catalyst for interdisciplinary practice and research - not only in sports nutrition and sports psychology - but across all sport and exercise disciplines.